2004
DOI: 10.1111/j.1365-2265.2004.02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum paraoxonase activity with insulin sensitivity and oxidative stress in hyperthyroid and TSH‐suppressed nodular goitre patients

Abstract: Iatrogenic thyroid hormone excess seems to mimic the effects of endogenous thyroid hormone excess on paraoxonase activity, insulin sensitivity and oxidative stress. These findings suggest that TSH suppression with levothyroxine may increase oxidative stress and LDL oxidation and thereby promote atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 28 publications
(51 reference statements)
6
44
4
1
Order By: Relevance
“…Increased HOMA and decreased Matsuda and Belfiore indices in HR and SHR patients compared with euthyroid subjects suggest that insulin resistance is present in both fasting and post-glucose state. Our results are in agreement with those of Yavuz et al (7,8) reporting significantly lower insulin sensitivity in a group of SHR. Interestingly, recent studies have shown that even subtle decreases in the levels of thyroid hormones within the physiological range negatively correlate with the HOMA index (16).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Increased HOMA and decreased Matsuda and Belfiore indices in HR and SHR patients compared with euthyroid subjects suggest that insulin resistance is present in both fasting and post-glucose state. Our results are in agreement with those of Yavuz et al (7,8) reporting significantly lower insulin sensitivity in a group of SHR. Interestingly, recent studies have shown that even subtle decreases in the levels of thyroid hormones within the physiological range negatively correlate with the HOMA index (16).…”
Section: Discussionsupporting
confidence: 83%
“…The studies in the literature regarding insulin resistance in SHR are scarce and controversial. Insulin sensitivity in patients with iatrogenic SHR has been reported to be either reduced (7,8) or unaltered (9).…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies conducted to date, those regarding insulin resistance in SHR are few and their results are controversial. Adamczyk et al only observed a weak impairment of insulin sensitivity that was associated with the lower activity of plasma paraoxonase [9,19]. Other authors, in their papers on iatrogenic SHR, describe a lower or unchanged level of insulin sensitivity.…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…2A), the resident macrophages of the liver (29,39). In man, hyperthyroidism is characterized by significant changes in circulating parameters related to oxidative stress, including (i) higher levels of lipid peroxidation indicators (40)(41)(42)(43)(44)(45)(46)(47)(48)(49); (ii) enhancement in hydrogen peroxide and lipid hydroperoxide levels (49); and (iii) diminished levels of antioxidants such as a-tocopherol (41), coenzyme Q (44), ascorbic acid (41), and reduced thiols (42,46,50). These changes correlated with the enhancement in urinary lipid peroxidation products (40) and chemiluminescence response (51) and are either significantly reduced or normalized by thyrostatic therapy or antioxidant supplementation (40-46, 49, 50).…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%